Current Awareness Services in Special Libraries and University Libraries - Siriwardena, P.L. (degree of Master of Library and Information Science, 2005)
This study investigates the present status of Current Awareness Services in Special Libraries and University Libraries in Sri Lanka, the availability of resources and the use of new technology to provide Current Awareness Services. The study also examined the librarians' attitudes towards Current Awareness Services and the problems encountered when providing Current Awareness Services to clientele. A total of 76 libraries were surveyed using a self completed questionnaire. The response rate was good with 75% of the libraries responding to the survey. The results highlights important issues with regard to Current Awareness Services as carried out by libraries in Sri Lanka. Although the librarian's attitude towards Current Awareness Services is favourable there is a lack of commitment on the part of librarians in providing a regular and planned Service focused on customer needs. Instead the librarians rely on informal and traditional methods to provide Current Awareness Services to their users. Technology has made little difference in the provision of Current Awareness Services with few libraries utilizing technology to provide Current Awareness Services. Although there are problems relating to funds and resources, libraries share the benefits of library cooperation in providing Current Awareness Services. The need for libraries to have staff with variety of skills and the need to utilize technological advantages is brought out in this study.